GLICOSAMINOGLICANO POLISULFATADO EN EL TRATAMIENTO DE OSTEOARTROSIS: RESUMEN EVALUACION CLINICA - Chávez Corrales, José (2024)
We evaluated prospectlvely the efficacy or polysulrutated glycosaminglycan (GAGPS) In the treatment or osteoarthrosis. We studied 91 patlents, 8S received tbe drug by Intramuscular route and 6 by lntranticular route. The lmprove were measured by pain on rest, pain on movement. stiffnes and functional lncapacity In all the patients a X-ray plain knees and routine laboratory tests. Our results show tbat more than 75% of patients haave a statistical significative lmprove in all the parameters evaluated. The mechanlsm or actions is by accumulation In the cartilage avolding the cartilage degradatlon. Tbe secondary slde effetcs were mild. We concluded that GAGPS are effectively a in tbe treatment of osteoarthrosis.